Development of Materials Teaching with Writing Text Drama Based on Problems In 9th of grade Student of Methodist High School 12 Medan - Aprina Sirait; Wisman Hadi; Biner Ambarita (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
The aim of this study to development of materials teaching writing text drama based on problems that happened in 9th of grade Students of Methodist Medan.  The reason for choosing this school student at Methodist Senior High School 12 Medan was because it had all the supporting aspects so that the research could run well. This study was conducted on July2019. The result is students who scored 65-74 were 2 with a percentage of 7%, at 55-64 there were 1 2 people with a percentage of 40 % and at 0-54 as many as 16 people with a percentage of 53%. In the posttest score increased better learning outcomes around 85-100 scores by 2 with a percentage of 7 %, 75-84 scores by 2 2 with a percentage of 73 %, a value of 65-74 by 6 with a percentage of 20 % . So, the final results of the needs analysis showed that 100% of teachers and students of Medan Methodist 12 High School needed a companion module in learning Indonesian.